La construción del fraude y los partidos políticos en la Argentina de los años treinta - Béjar Puche, María Dolores (Centro de Investigaciones Socio Históricas. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2004)
In this work is reconstructed the trajectory of the fraudulent regime during the Agustin Justoïs government (1932-1938). The constraint actions carried out by the "caudillos" in the election day were its most evident characteristic, but the construction of the fraud had a deeper reach. Along this experience, the constraint over the most important opponent party and the denial of the citizenïs rights were accompanied by the reorganization of the State to obtain the subordination of the Judicial and the Legislative Power to the government crew. This text identifies the practices and decisions of the opposition and governing parties in relation with this process.